2005
DOI: 10.1159/000082884
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Antioxidants Are Not Associated with Alzheimer’s Disease or Cognitive Decline

Abstract: Antioxidants prevent oxidative stress that possibly causes neuronal loss in Alzheimer’s disease (AD). We examined whether high plasma levels of the antioxidant vitamins A and E were associated with lower prevalence of AD or cognitive decline (CD). We performed a cross-sectional study within the Rotterdam Study. In an univariate model, higher levels of vitamins A and E were significantly associated with lower prevalence of AD. However, when additional adjustments were made for important confounders, such as age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 42 publications
4
31
0
1
Order By: Relevance
“…Likewise, some longitudinal studies revealed that lower erythrocyte EPA and DHA levels were associated with a higher risk of cognitive decline [15,16]. However, this association could not be confirmed by other studies [17,18,19]. …”
Section: Introductionmentioning
confidence: 91%
“…Likewise, some longitudinal studies revealed that lower erythrocyte EPA and DHA levels were associated with a higher risk of cognitive decline [15,16]. However, this association could not be confirmed by other studies [17,18,19]. …”
Section: Introductionmentioning
confidence: 91%
“…In addition, animal models have demonstrated that dietary supplementation with antioxidant vitamins can decrease oxidative stress and either prevent or reverse the age-related changes in cognitive functions (198,314,352,451). Clinical trials, however, have produced conflicting results concerning the therapeutic efficacy of antioxidant supplementation during AD (121,122,258). Similar to the conflicting results of antioxidant therapy during physiological aging, this discrepancy may be due to multiple factors such as reduced bioavailability and=or poor specificity of these treatment regimens.…”
Section: B Ros In Admentioning
confidence: 99%
“…They performed a cross-sectional study within another AD study and found that if a univariate model was used, high plasma vitamin A and E could be correlated to lower cognitive decline. However, when adjustments were made with respect to age, gender, and total cholesterol, the correlation weakened, and it was concluded that there was no association between plasma levels of vitamin A and E and cognitive decline (122). The same question was examined in a cohort of elderly woman and no correlation between plasma carotenoids and tocopherols and cognitive deficits was observed (206).…”
mentioning
confidence: 99%
“…Interestingly, three other studies also found low vitamin E levels were associated with an increased risk of AD and VaD, but the association disappeared after controlling for cholesterol levels [153,157,163] . In contrast, three case-control studies did not fi nd associations between vitamin E and dementia [150,164] or AD [152,165] . Only one nested case-control study within a prospective cohort has been conducted [166] .…”
Section: Epidemiological Studiesmentioning
confidence: 99%